2005
DOI: 10.1682/jrrd.2005.01.0008
|View full text |Cite
|
Sign up to set email alerts
|

Hair cell regeneration: An exciting phenomenon . . . But will restoring hearing and balance be possible?

Abstract: Abstract-Sensory hair cells of the inner ear are susceptible to damage from a variety of sources including aging, genetic defects, and environmental stresses such as loud noises or chemotherapeutic drugs. Unfortunately, the consequence of this damage in humans is often permanent hearing/balance problems. The discovery that hair cells can regenerate in birds and other nonmammalian vertebrates has fueled a wide range of studies that are designed to find ways of restoring hearing and balance after such damage. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 114 publications
0
14
0
1
Order By: Relevance
“…In contrast, lost HCs are not normally replaced in the traumatized mammalian cochlea (Holley, 2005;Matsui and Ryals, 2005). However, there is a small but significant spontaneous renewal of HCs occurring in the vestibular sensory epithelia of several mammalian species, as demonstrated in vivo for guinea pig and chinchilla and in vitro for rat after ototoxic injury (Forge et al, 1993;Tanyeri et al, 1995;Berggren et al, 2003;Cunningham and Brandon, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, lost HCs are not normally replaced in the traumatized mammalian cochlea (Holley, 2005;Matsui and Ryals, 2005). However, there is a small but significant spontaneous renewal of HCs occurring in the vestibular sensory epithelia of several mammalian species, as demonstrated in vivo for guinea pig and chinchilla and in vitro for rat after ototoxic injury (Forge et al, 1993;Tanyeri et al, 1995;Berggren et al, 2003;Cunningham and Brandon, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…If so, this could have masked any differential hearing loss in musicians in this study. There is also well-established evidence that some individuals may have a greater genetic susceptibility to hearing loss [9,10]. The findings may represent an element of a healthyworker effect.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, pDCs express tolerogenic phenotype and induce Treg cell through the expression of IDO [61][62][63][64]. In vivo study further showed that selective ablation of DCs led to the loss of FoxP3-expressing Treg and the development of proinflammatory autoreactive T effectors, resulting in excessive autoimmunity [65].…”
Section: Effect Of Toldcs On Regulatory T Cells (Treg)mentioning
confidence: 99%